2020
DOI: 10.1016/j.jbiomech.2020.109635
|View full text |Cite
|
Sign up to set email alerts
|

The sensitivity of joint kinematics and kinetics to marker placement during a change of direction task

Abstract: The conventional gait model (CGM) refers to several closely related biomechanical models used in the objective analysis of human motion. Their use has become popular in the analysis of change of direction tasks to inform best practice in the prevention and rehabilitation of anterior cruciate ligament injury. As externally-placed markers define segment axes origins and orientations, kinematic and kinetic outputs from the CGM are sensitive to marker placement. The aim of this investigation was to quantify the se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 44 publications
3
13
0
Order By: Relevance
“…Errors are likely to vary at different times, which was also highlighted by the reference trail comparison as most IMC (except rotation) measures examined were within the benchmark. This is in line with previous studies [25,28].…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Errors are likely to vary at different times, which was also highlighted by the reference trail comparison as most IMC (except rotation) measures examined were within the benchmark. This is in line with previous studies [25,28].…”
Section: Discussionsupporting
confidence: 94%
“…Errors or inconsistencies (e.g., due to differences in thickness of subcutaneous fat) in the placement of markers relative to target anatomical landmarks is thus the single greatest contributor to measurement variability in contemporary clinical gait analysis [22]. It affects the kinematic measures by up to 15 degrees in the sagittal plane, 15 degrees in the transversal plane and 17 degrees in the transverse plane [22][23][24][25][26]. In interpreting the accuracy and precision found for the IMC system in this study, we compared the bias and RMSD to those previously reported for MMC-based systems, resulting from marker placement error within, and between, assessors ( Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…This allows three-dimensional (3D) assessment during both static positions and dynamic conditions, including daily life motor tasks ( Schmid et al, 2016 ; Diebo et al, 2018 ; Severijns et al, 2020 , 2021 ). However, the validity and accuracy of such skin marker-based methods is highly dependent on correct marker placement, which is known to be one of the main sources of variability in kinematic results ( Della Croce et al, 2005 ; Gorton et al, 2009 ; McFadden et al, 2020 ). Nevertheless, information on spinal marker placement accuracy (i.e., palpation error) and its possible effect on spinal alignment measurements, in both healthy and deformed spines, is scarce.…”
Section: Introductionmentioning
confidence: 99%
“…However, despite reported sub-millimetre accuracy, marker-based motion capture systems are subject to the limitation of soft tissue artefact and muscle contraction that affect the resultant knee kinematics (Fiorentino et al, 2017;Schulz & Kimmel, 2010). Soft tissue artefact (STA), being site, participant and movement task-specific, will impact upon the selection of marker locations and the subsequent biomechanical model utilised (Benoit et al, 2006;Cockcroft et al, 2016;McFadden et al, 2020;Schulz & Kimmel, 2010). The use of bone pins or advanced imaging validation methods to optimise kinematic data (Fiorentino et al, 2017;Mentiplay & Clark, 2018;Potvin et al, 2017) is impractical in sports settings.…”
Section: Introductionmentioning
confidence: 99%